A model for thin shells in the combined finite-discrete element method. Issue 1 (5th March 2018) - Uzelac, Ivana; Smoljanovic, Hrvoje; Batinic, Milko; Peroš, Bernardin; Munjiza, Ante
Abstract : Purpose: This paper aims to present a new numerical model for geometric nonlinear analysis of thin-shell structures based on a combined finite-discrete element method (FDEM). Design/methodology/approach: The model uses rotation-free, three-node triangular finite elements with exact formulation for large rotations, large displacements in conjunction with small strains. Findings: The presented numerical results related to behaviour of arbitrary shaped thin shell structures under large rotations and large displacement are in a good agreement with reference solutions. Originality/value: This paper presents new computationally efficient numerical model for geometric nonlinear analysis and prediction of the behaviour of thin-shell structures based on combined FDEM. The model is implemented into the open source FDEM package "Yfdem", and is tested on simple benchmark problems.